Implementation of the Transformational Leadership Style of the Head of Apparatus Performance and Awards at the Regional Civil Service Agency of South Sulawesi Province - St. Ramlah; Sitti Hardiyanti Arhas; Isgunandar Isgunandar (ASHA Publishing, 2024)
This study aims to determine the Application of Transformational Leadership Style of the Head of Apparatus Performance and Awards in the Regional Civil Service Agency of South Sulawesi Province. The approach and type of research used are qualitative approaches and descriptive research types, while the informants in this study are the Sub-Coordinator of each Apparatus Performance and Awards Division and employees of the Apparatus Performance and Awards Division at the Regional Civil Service Agency of South Sulawesi Province. The data collection techniques carried out are using observation, interview, and documentation methods. The data analysis techniques used are data condensation, data presentation, and conclusion drawn. The results of this study show that all indicators used in the research on the Implementation of Transformational Leadership Style of the Head of Apparatus Performance and Awards at the Regional Civil Service Agency of South Sulawesi Province are classified as good. The indicators in question are Ideal Influence which is classified in the good category which is supported by always respectful behavior, more concerned with work than personal affairs, and communicating well in terms of making decisions. Inspirational Motivation is classified as a good category which is supported by consistent behavior in providing motivation, in conveying something achieved enthusiastically, an effective vision, and in building good cooperation with employees. Intellectual Stimulation is classified as a good category which is supported by the behavior of developing ideas from employees, providing solutions to problems, and encouraging employees to be creative and innovative. Paying Attention to Individuals is classified as good because of their behavior in giving advice, implementing a personal approach, listening to every suggestion or problem of subordinates well, and paying attention to the needs of employees